TERAPI HYPNOBREASTFEEDING UNTUK MENURUNKAN KECEMASAN IBU POSTPARTUM - Jannah, Miftahul; Putri Heriyanti , Khotijah; Abd Hafid, Rachmawati; Aidina, Dyka (Universitas Batam, 2024)
Anxiety in postpartum women is not uncommon, with a number of signaling mental-related issues, such as tenseness, worry, and/or panic attacks, may appear. Its negative impacts are not only limited to affecting the mother’s mental state, but also the baby’s proper growth and well-being.. This study aims to provide a standardized Continuity of Midwifery Care (CoMC) along with its complementary effort on Mrs. E (aged 30) who gave birth in the Hospital of Hj. Bunda Halimah in 2024. The design of the study employs a study case. CoMC coverage started from the antenatal, intranatal, neonatal, postnatal, and Family Planning (FP) through contraceptive proposition on Mrs. E (G1P0A0) whose last menstrual period (LMP) was on 16 June 2023 and the expected delivery date (EDD) was on 23 March 2024. The first contact took place on 27 February 2024 during the last trimester of pregnancy (p. 36 weeks, 3 days) with nil remarks, no signs of difficulty, and was followed by intranatal care on 31 March 2024, via c-section. The newborn was reportedly normal with no signs of abnormalities. Postnatal care showed a sign of anxiety which was anticipated by a series of hypnobreastfeeding technique, conducted four times, with the hopes to stimulate and to help relax the mother to make breastfeeding activity come out as natural as possible.